Multiple contexts of exposure: Activity spaces, residential neighborhoods, and self-rated health. (December 2015) - Sharp, Gregory; Denney, Justin T.; Kimbro, Rachel T.
Abstract: Although health researchers have made progress in detecting place effects on health, existing work has largely focused on the local residential neighborhood and has lacked a temporal dimension. Little research has integrated both time and space to understand how exposure to multiple contexts – where adults live, work, shop, worship, and seek healthcare – influence and shape health and well-being. This study uses novel longitudinal data from the Los Angeles Family and Neighborhood Survey to delve deeper into the relationship between context and health by considering residential and activity space neighborhoods weighted by the amount of time spent in these contexts. Results from multilevel cross-classified logistic models indicate that contextual exposure to disadvantage, residential or non-residential, is independently associated with a higher likelihood of reporting poor or fair health. We also find support for a contextual incongruence hypothesis. For example, adults living in the most disadvantaged neighborhoods are more likely to report poor or fair health when they spend time in more advantaged neighborhoods than in more disadvantaged ones, while residents of more advantaged neighborhoods report worse health when they spend time in more disadvantaged areas. Our results suggest that certain types of place-based cumulative exposures are associated with a sense of relative neighborhood deprivation that potentially manifests in worse health ratings. Highlights: Residential and activity space disadvantage independently affect self-rated health. We find evidence of a contextual incongruence hypothesis. Residents who live and spend time in very dissimilar places report worse health. Activity space disadvantage mediates the health effects of residential disadvantage. Exposure to activity space disadvantage matters more for residents of disadvantaged areas.